The use of BIM in FM: Legal aspects in the context of the BIM BR strategy - Duque, Marcos André; Ferneda, Edilson; Silva, Ana Paula Bernardi da; Streit, Rosalvo Ermes; Scheer, Sergio (National Journal of City Management, 2023)
The BIM BR Strategy, also known as the National Strategy for BIM Dissemination in Brazil, aims to promote an environment conducive to investment in BIM and its widespread adoption across the country. In its gradual implementation plan, the year 2028 has been set as the starting point for utilizing BIM in the management and maintenance of projects after their construction. This research seeks to provide Facility Management (FM) leaders, both in the public administration and private companies, with a comprehensive overview of the need, current status, and potential of using BIM in FM to achieve the 2028 goal of the BIM BR Strategy from the perspective of legal aspects involved.